Transformations of a community organization based on its involvement in the provision of a public service: the case of Ecofuturo - Blanco-Moreno, Carolina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2018)
The purpose of this article is to analyze the transformations in the organizational process of Ecofuturo, a community organization located in Bolívar - Valle del Cauca, based on its relationship with the local government in the management of solid waste in the municipality. Describes the relationship built with the local government during the 8 years in which the organization was in charge of this service and the transformations of the organization as a result of the development of this activity. This article is the product of the research project "Following the traces of Ecofuturo: Transformations of the organization based on its link with the local government in the management of solid waste in the Municipality of Bolívar - Valle".